Analysis of agricultural meteorological disasters in Shaanxi Province from 1981 to 2018 and their impact on grain production - Chunlin Wang; Yufei Xiong (E3S Web of Conferences, 2020)
This paper studied the change characteristics of four types of agricultural meteorological disasters such as flood, drought, hail and freeze and their impact on the total grain yield of Shaanxi Province. Based on the agricultural statistical data of Shaanxi Province from 1981 to 2018, the disaster-affected rate, disaster-suffered rate and disaster intensity index, as well as the grey correlation analysis method were used to analyze the agricultural meteorological disasters and their impact on grain yield in Shaanxi Province from 1981 to 2018. The results show that drought has the largest disaster-affected area and disaster-suffered area in Shaanxi Province, but the disaster-affected rate and disaster-suffered rate increases first and then decreases. The difference of disaster intensity among flood, drought and hail is relatively small, among which the drought disaster has the strongest disaster intensity and the freeze has a relatively weak disaster intensity. The grey correlation analysis show that the affected area of hail disasters has the greatest impact on the total grain yield of Shaanxi Province, followed by drought and flood, and the affected area of freeze disaster has a relatively small impact on the total grain yield.